Histopathology in Pacific oyster (Crassostrea gigas) spat caused by the dinoflagellate Prorocentrum rhathymum - Pearce, I; Handlinger, JH; Gustaaf Hallegraeff (2005)
The recognition of an apparent association between seasonal oyster spat mortalities (up to 40%) and high Prorocentrum rhathymum density in the Little Swanport Estuary, Tasmania, prompted further experimental investigation into the toxicity by this dinoflagellate. Standard brine shrimp, haemolysis assays and intraperitoneal mouse bioassays revealed fast acting toxins in methanol but not aqueous extracts of P. rhathymum, with mice dying in less than 20 min. Oyster bioassays involved feeding spat (4 mm shell width) for 21 consecutive days on a diet of cultured P. rhathymum at simulated bloom densities (10 4 cells ml -1). No oyster mortality was observed, however, histopathological signs of thin, dilated gut tubules and sloughing of gut cells resembled those seen in affected field samples. In contrast to field samples, gill pathology was also observed in experimental exposure oysters. Â© 2003 Elsevier B.V. All rights reserved.